2021
DOI: 10.3390/pr9112028
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling and Multi Objective Optimization Analysis of Heavy Vehicle Chassis

Abstract: The primary supporting structure of an automobile and its other vital systems is the chassis. The chassis structure is required to bear high shock, stresses, and vibration, and therefore it should possess adequate strength. The objective of current research is to analyze a heavy motor vehicle chassis using numerical and experimental methods. The CAD design and FE analysis is conducted using the ANSYS software. The design of the chassis is then optimized using Taguchi design of Experiments (DOE); the optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A sparse matrix solver is used to perform the simulation after the loads and boundary conditions have been established. This is carried out in order to eliminate the sequential step that organizes equations at each iteration and to reuse the same matrix structure throughout the simulation [18]. The There are matrices created for every element.…”
Section: Methodsmentioning
confidence: 99%
“…A sparse matrix solver is used to perform the simulation after the loads and boundary conditions have been established. This is carried out in order to eliminate the sequential step that organizes equations at each iteration and to reuse the same matrix structure throughout the simulation [18]. The There are matrices created for every element.…”
Section: Methodsmentioning
confidence: 99%
“…The solution stage involves element matrix formulations, assemblage of global stiffness elements followed by inversions and multiplications [21]. The final stage is post processing which involves viewing and editing of results where the chassis specifications were obtained from [17].…”
Section: Methodsmentioning
confidence: 99%
“…The aim of present paper is to perform a structural analysis of a heavy motor vehicle chassis & optimize it using different optimization methods to reduce the weight using Reinforced Aluminium-Matrix Composites Al6092/SiC/17.5p MMC. The appropriate data of an existing heavy duty truck chassis of TATA company's model number 1612 (material used St52 E=2.10 x 10 5 N / mm 2 ) as a simply supported beam with overhang ladder frame is taken for design and analysis with Side bar of the chassis made from 'C' Channels having dimensions 116mm x 25mm x 5 mm [17]. Total load acting on the chassis is 257022N [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aiming at the problem of TM1314 American trailers axle (referred to as axle) being overweight, first, parametric model of the axles is established and finite element analysis is carried out in this paper based on multiconstraints. Second, the Pareto optimal solution set of the multiobjective optimization of the axle was obtained through the MOGA, which is suitably used to solve the system reliability and multiobjective problems (Wang et al , 2022; Xie et al , 2011; Li et al , 2021; Agarwal and Mthembu, 2021). Finally, the specimens were trial-produced to carry out bench verification tests, which showed that the weight was reduced on the premise of not decreasing the original mechanical performance requirements and design standards.…”
Section: Introductionmentioning
confidence: 99%